Exploring Science Proficiency and High Order Thinking Primary School Students in Savannakhet Province: https://doi.org/10.69692/SUJMRD0901229 - LASASAN, Insong (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research aimed 1) to study the science proficiency of 3rd grade students and 2) to study high order thinking (HOT) ability in science. The population consisted of 135 students from six schools in Kaisonephomvihane city. The data was collected from students with multiple choices and open questions based on science and environment subject. The data was analyzed to fine the percentage, mean and standard deviation. The result indicated that the average of science proficiency of students was very low ( ) or 31% of the total scores, Students who have HOT abilities in science were 22.59 % of total students. Based on the result, training of teachers for improving teaching science should be provided to primary school teachers.